2016
DOI: 10.3892/mmr.2016.4780
|View full text |Cite
|
Sign up to set email alerts
|

Association of HNF4α gene polymorphisms with susceptibility to type 2 diabetes

Abstract: The present study aimed to explore the association between single nucleotide polymorphisms (SNPs) in the hepatocyte nuclear factor‑4α (HNF‑4α) gene and the incidence of type 2 diabetes in the Chinese Bai population in Dali city, China. The polymerase chain reaction‑restriction fragment length polymorphism method was used to analyze four SNPs (rs4810424, rs1884613, rs1884614 and rs2144908) in the HNF‑4α gene in 44 patients with type 2 diabetes and 87 healthy controls in Chinese Bai individuals. The haploid type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…5). In addition to IBD, human HNF4A variants are associated with metabolic syndrome (Weissglas-Volkov et al 2006) and type 2 diabetes (Ma et al 2016). Interestingly, microbiota have also been implicated in both of these diseases (Qin et al 2012;Vrieze et al 2012), raising the possibility that microbiota suppression of HNF4A trans activity could play a role in these diseases as well.…”
Section: Discussionmentioning
confidence: 99%
“…5). In addition to IBD, human HNF4A variants are associated with metabolic syndrome (Weissglas-Volkov et al 2006) and type 2 diabetes (Ma et al 2016). Interestingly, microbiota have also been implicated in both of these diseases (Qin et al 2012;Vrieze et al 2012), raising the possibility that microbiota suppression of HNF4A trans activity could play a role in these diseases as well.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results were derived from unadjusted estimations, and failure to conduct further adjusted analyses for baseline characteristics of participants such as age, gender and co-morbidity conditions may influence the veracity of our findings [20, 21]. Secondly, significant heterogeneities were detected in certain subgroup comparisons, which indicated that the inconsistent results of included studies could not be fully explained by differences in ethnic background, and other unmeasured characteristics of participants may also partially attribute to between-study heterogeneities [22]. Thirdly, since only published articles were eligible for analyses, although funnel plots revealed no obvious publication biases, we still could not rule out the possibility of potential publication biases [23].…”
Section: Discussionmentioning
confidence: 99%
“…The results were consistent with previous studies that promoter variants rs266729 and rs17300539 polymorphisms in ADIPOQ gene, rs2144908 and rs4810424 polymorphisms in HNF4A gene were associated with T2D risk. Silvia 58 reported that the risk allele of rs1884614 of HNF-4A was significantly associated with increased risk of T2D, while no significant association in our analysis when new publications 19,[62][63][64][65] were included. Silvia also reported that the risk allele of rs1884613 of HNF4A was significantly associated with increased risk of T2D, it was significantly associated with increased risk of T2D when the HWE deviation excluded only.…”
Section: Discussionmentioning
confidence: 72%
“…Some association studies of genetic variants in promoter region and T2D risk have been reported . However, previous studies were limited to small number of individual genetic variants and insufficient sample size . In addition, effects of the study populations and demographic characteristics were often neglected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation